2010
DOI: 10.1002/jobm.200900162
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental conditions on extracellular lipases production and fungal morphology from Aspergillus niger MYA 135

Abstract: Under the current assay conditions, lipase production in mineral medium was only detected in the presence of vegetable oils, reaching the highest specific activity with olive oil. In this way, effect of different environmental conditions on fungal morphology and olive oil-induced extracellular lipases production from Aspergillus niger MYA 135 was studied. It was observed that addition of 1.0 g l(-1) FeCl(3)to the medium encouraged filamentous growth and increased the specific activity 6.6 fold after 4 days of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…Thus, as it was mentioned before, the addition of 1 g l -1 FeCl 3 to the BM encourages a scarcely branched mycelium and increases the production of both a mycelium-bound transesterification lipase activity (Colin et al 2011) and an emulsifier compound (Colin et al 2010a). Interestingly, in the same medium supplemented with 2% olive oil it was also observed that a specific extracellular hydrolytic lipase activity was increased by 6.6 fold after four days of incubation compared to the control (Colin et al 2010b). Finally, another application is the enhancement of protoplast formation in Phaffia rhodozyma .…”
Section: Discussionmentioning
confidence: 94%
“…Thus, as it was mentioned before, the addition of 1 g l -1 FeCl 3 to the BM encourages a scarcely branched mycelium and increases the production of both a mycelium-bound transesterification lipase activity (Colin et al 2011) and an emulsifier compound (Colin et al 2010a). Interestingly, in the same medium supplemented with 2% olive oil it was also observed that a specific extracellular hydrolytic lipase activity was increased by 6.6 fold after four days of incubation compared to the control (Colin et al 2010b). Finally, another application is the enhancement of protoplast formation in Phaffia rhodozyma .…”
Section: Discussionmentioning
confidence: 94%
“…Effects of the culture conditions on biomass concentration from A. niger Previously, we reported on the effect of environmental factors in the biomass concentration from A. niger MYA 135, when cultured in the presence of 2% olive oil [9]. In the present work, fungal growth in the media without olive oil is also described (Fig.…”
Section: +2mentioning
confidence: 73%
“…In previous studies we found that extracellular lipases production from A. niger MYA 135 was strongly affected by the initial culture conditions [9]. However, naturally immobilized catalysts such as cell-bound microbial lipases have advantages over their extracellular counterparts, and have recently been receiving increased attention [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since the production, chemical compositions and functional properties of the bioemulsifiers can be strongly influenced by environmental factors, in this study the effect of culture conditions on the emulsifier production by Aspergillus niger MYA 135 was tested. In previous studies performed on this strain, it was found that the fungal growth and metabolites production such as citric acid (Pera and Callieri 1997) and extracellular lipases (Colin et al 2010) were strongly affected by the initial pH of the culture medium, the incubation temperature and by the presence of CaCl 2 or FeCl 3 in the medium. In this study, only at an initial pH 2.0 or in the BM supplemented with FeCl 3 the production of bioemulsifiers was significantly increased compared to the reference conditions (P \ 0.05) (Fig.…”
Section: Resultsmentioning
confidence: 98%